Pengaruh Pelaksanaan Good Corporate Governance dan Leverage Terhadap Kinerja Keuangan (Studi Kasus Perusahaan Perbankan Yang Terdaftar Di Bei Tahun 2016-2018) - Therito Akbar Firmansyah; Ronny Malavia Mardani; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2020)
AbstrakThis research was conducted with the aim of 1) to find out how the influence of independent commissioners on financial performance, 2) to find out the audit committee on financial performance, 3) to determine the leverage on financial performance. The independent variable in this study is the independent commissioner, audit committee, and leverage, while the dependent variable is finance. This type of research is explanatory. The data used in the form of secondary data. The population and sample are all banking companies listed on the Indonesia Stock Exchange in 2016-2018. With data on 42 banking companies listed on the IDX, and data on 28 banking companies are obtained. The sampling technique is to use purposive sampling techniques and data testing techniques used in this study normality test, classic assumption test, multiple linear regression analysis and hypothesis testing.With the results of the analysis that has been processed through SPSS shows that independent commissioners have a positive effect on financial performance, the audit committee does not have a positive effect on financial performance and leverage has a negative effect on financial performance.Keywords : Good Corporate Governance, Leverage, dan Financial Performance.